Tumor Resistance Explained by Hormesis - Edward J. Calabrese Ph.D; Marc A. Nascarella Ph.D (SAGE Publishing, 2010)
Enhanced drug (GDC 0449) resistance in a mouse model for human medulloblastoma is shown in the present paper to act via an hormetic response. This has significant implications, imposing constraints on the quantitative features of the dose response of the chemotherapeutic agent, affecting optimal study design, mechanism assessment strategy, potential for tumor rebound, patient relapse and disease outcome.